Optimization of Complexity in Big Data: The Query Response Time - Bhawan Chaudhary, Santosh Kumar, Shweta Dwivedi (International Journal of Advanced Science and Technology, 2020)
Due to the increasing size of databases, organizations motivated and moved their huge volume of data into big databases which is huge in volume and variety of data model. It is quite difficult to querying and analyzing the big data of an organization. The data distribution centers should have the option to fulfil the demand of data. With new prerequisites it is essential to have close to genuine occasions reaction from the large information assembled. All the information can’t be fit in to one specific database "One Size Does Not Fit All" since information starting from sources have various arrangements. In this paper, we compute the response time of a fuzzy query performed on the designed big database and optimize the time of query that produce the output in minimal time, the time complexity of query response time algorithm is also discussed and computed.